Coworking in Lisbon: Experiences of collaboration and sharing on changing urban contexts - Morgado, S. (2021)
As innovative and creative ecosystems, Coworking Spaces (CWS) show high adaptability and recovery capacity in facing global event disruptions. This article is an exploratory study that aims to approach the development of coworking spaces in the city of Lisbon. It investigates the location patterns and adaptation of such ecosystems in Lisbon, by mapping the phenomenon and examining its spatio-temporal dynamics that was influenced by the urbanisation phases of the city, as well as the development and planning policies designed over the years. Starting from a broader view of CWS location in the city, this article moves on to present two particular cases, implemented in a different time and socio-economic circumstances in different parts of the city: LxFactory and The Creative Hub. This study is part of a broader contribution to COST Action (CA)18214 "The geography of the new workspaces and the impact on the periphery".